Motor fatigue measurement by distance-induced slow down of walking speed in multiple sclerosis. - Rémy Phan-Ba; Philippe Calay; Patrick Grodent; Gael Delrue; Emilie Lommers; Valérie Delvaux; Gustave Moonen; Shibeshih Belachew (PLoS ONE, 2012)
BACKGROUND AND RATIONALE: Motor fatigue and ambulation impairment are prominent clinical features of people with multiple sclerosis (pMS). We hypothesized that a multimodal and comparative assessment of walking speed on short and long distance would allow a better delineation and quantification of gait fatigability in pMS. Our objectives were to compare 4 walking paradigms: the timed 25-foot walk (T25FW), a corrected version of the T25FW with dynamic start (T25FW(+)), the timed 100-meter walk (T100MW) and the timed 500-meter walk (T500MW). METHODS: Thirty controls and 81 pMS performed the 4 walking tests in a single study visit. RESULTS: The 4 walking tests were performed with a slower WS in pMS compared to controls even in subgroups with minimal disability. The finishing speed of the last 100-meter of the T500MW was the slowest measurable WS whereas the T25FW(+) provided the fastest measurable WS. The ratio between such slowest and fastest WS (Deceleration Index, DI) was significantly lower only in pMS with EDSS 4.0-6.0, a pyramidal or cerebellar functional system score reaching 3 or a maximum reported walking distance ≤ 4000 m. CONCLUSION: The motor fatigue which triggers gait deceleration over a sustained effort in pMS can be measured by the WS ratio between performances on a very short distance and the finishing pace on a longer more demanding task. The absolute walking speed is abnormal early in MS whatever the distance of effort when patients are unaware of ambulation impairment. In contrast, the DI-measured ambulation fatigability appears to take place later in the disease course.